2017
DOI: 10.1080/13696998.2017.1296453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of economic and clinical outcomes between patients undergoing laparoscopic bariatric surgery with powered versus manual endoscopic surgical staplers

Abstract: Aims: To compare economic and clinical outcomes between patients undergoing laparoscopic Rouxen-Y gastric bypass (LRY) or laparoscopic sleeve gastrectomy (LSG) with use of powered vs manual endoscopic surgical staplers. Materials and methods: Patients (aged !21 years) who underwent LRY or LSG during a hospital admission (January 1, 2012-September 30, 2015 were identified from the Premier Perspective Hospital Database. Use of powered vs manual staplers was identified from hospital administrative billing records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Powered endoscopic staplers reportedly lead to fewer bleeding events during pulmonary vessel transection than manual endoscopic staplers due to increased stability during firing. 3,4 Miller et al also found that powered staplers demonstrate superior results in reduced total hospital length of stay and total hospital cost in addition to bleeding management; however, this study was limited by differences in patient characteristics and different approaches in multiple centers and/or surgeons' experience, making it difficult to draw clear conclusions about the full benefits of powered versus manual staplers. 4 Our results, from a single center, demonstrate that tremors during firing may not be the leading cause of bleeding during vessel transection.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Powered endoscopic staplers reportedly lead to fewer bleeding events during pulmonary vessel transection than manual endoscopic staplers due to increased stability during firing. 3,4 Miller et al also found that powered staplers demonstrate superior results in reduced total hospital length of stay and total hospital cost in addition to bleeding management; however, this study was limited by differences in patient characteristics and different approaches in multiple centers and/or surgeons' experience, making it difficult to draw clear conclusions about the full benefits of powered versus manual staplers. 4 Our results, from a single center, demonstrate that tremors during firing may not be the leading cause of bleeding during vessel transection.…”
Section: Discussionmentioning
confidence: 88%
“…Results from a real-world study on laparoscopic bariatric surgery found ECHELON powered staplers were associated with a 47% lower rate of bleeding complications versus Medtronic Endo-GIA TM with Tri-Staple TM Technology and other manual staplers. 3 Additionally, in vivo experiments in a gastrointestinal porcine model reported A B C Figure 1 (A) Comparison of powered endoscopic staplers (B) comparison of jaw angles and (C) histological findings after pulmonary arterial stapling. Histological sections of pulmonary artery tissue adjacent to the area of stapling were stained with Elastica van Gieson stain (X200).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even within the same surgical procedure, technique may also influence bleeding. For example, less bleeding was observed in 1 study with the use of a powered versus automatic stapler in bariatric surgery [38] . The difference in result may also be related to the definition of bleeding used between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Powered linear staplers have been shown to consistently produce fewer malformed staples [5,6]. The advantage of power has been shown to carry over to superior performance clinically [7][8][9][10][11] and even provide an economic benefit [12].…”
Section: Introductionmentioning
confidence: 99%